2017
DOI: 10.1177/1474515117690297
|View full text |Cite
|
Sign up to set email alerts
|

Effects of yoga versus hydrotherapy training on health-related quality of life and exercise capacity in patients with heart failure: A randomized controlled study

Abstract: Yoga may be an alternative or complementary option to established forms of exercise training such as hydrotherapy for improvement in health-related quality of life and may decrease depressive symptoms in patients with heart failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0
7

Year Published

2018
2018
2025
2025

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(62 citation statements)
references
References 30 publications
0
55
0
7
Order By: Relevance
“…The 1006 males (67.1%) averaged 60.2 years of age and the 493 females (32.9%) averaged 61.3 years of age. In terms of NYHA class, the largest number of studies (11 RCTs; 35.5%)[32-42] targeted NYHA class II-III patients and the second largest number (5 RCTs; 16.1%)[43-47] targeted NYHA class I-III patients. The duration of the respiratory training interventions in the 31 RCT studies ranged between 4 wk and 24 wk, with the largest number (15 RCTs, 48.4%)[18,32,38,40,42,45-54] lasting for 12 wk, followed by 5 RCTs (16.1%) with interventions that lasted for 8 wk[34,43,44,55,56] and 10 wk[35-37,41,57], respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The 1006 males (67.1%) averaged 60.2 years of age and the 493 females (32.9%) averaged 61.3 years of age. In terms of NYHA class, the largest number of studies (11 RCTs; 35.5%)[32-42] targeted NYHA class II-III patients and the second largest number (5 RCTs; 16.1%)[43-47] targeted NYHA class I-III patients. The duration of the respiratory training interventions in the 31 RCT studies ranged between 4 wk and 24 wk, with the largest number (15 RCTs, 48.4%)[18,32,38,40,42,45-54] lasting for 12 wk, followed by 5 RCTs (16.1%) with interventions that lasted for 8 wk[34,43,44,55,56] and 10 wk[35-37,41,57], respectively.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 13 RCTs (41.9%)[18,33,34,42,45-47,49,54-58] described random sequence generation and 9 (29.0%)[18,33,38,39,47,49,51,54,57] described allocation concealment. With the regard to blinding, 4 RCTs (12.9%)[33,45,47,54] blinded the participants and 14 (45.2%)[18,33,36,37,41,43-45,50-54,57] blinded the data collectors. The average dropout rate of participants was 12%, with 7 RCTs reporting a rate in excess of 20%[18,34,47,49,50,53,57].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…12 A growing body of literature exists on the effectiveness of a variety of exercise interventions for patients with HF in which nurses maintain a key role, such as a cardiac rehabilitation program for HF patients, 30 home walking programs, [31][32][33][34] home-based telemonitored cardiac rehabilitation, 35,36 tai chi 37,38 and yoga. 39,40 Other interventions that have been tested for effects to improve patient outcomes in HF include those aimed at improving cognitive function. In preliminary studies, cognitive training led to small improvements in cognitive function, 41,42 as well as positive effects on engagement in HF self-care 43 and functional outcomes such as instrumental activities of daily living (e.g., medication taking, grocery shopping) that may result in reduced healthcare costs.…”
Section: Nursing Interventions To Improve Outcomesmentioning
confidence: 99%
“…It is also a known fact that aquatic therapy can help stroke patients or people with neurological logic disorders to enhance and obtain optimum mobility [12] [8] . Aquatic exercises for stroke patients using water as resistance involves the arm muscles, shoulders, back, stomach, and feet [13] . The systematic reviews regarding the effectiveness of aquatic therapy showed that it improved the dynamic balance and walking speed of stroke patients [12] .…”
Section: Introductionmentioning
confidence: 99%